COVID-19 vaccines as a game-changing tool? A corpus-based study of vaccine communication in People's Daily and The New York Times - Zhihan Wen; Ming Liu; Changpeng Huan (Heliyon)
The global discourse on COVID-19 has shifted from a broad discussion of the pandemic to a focus on the vaccine. However, how COVID-19 vaccines have been discursively constructed and communicated in mainstream newspapers has received insufficient scientific attention, particularly given that research indicates the news media is a more reliable source of vaccine information compared to social media platforms. Considering the significance and potential consequences of the fierce strategic rivalry between the U.S. and China, this study integrates corpus linguistics and critical discourse analysis to examine the discursive construction of COVID-19 vaccines in two leading newspapers from both countries: People's Daily and The New York Times. Our findings reveal both similarities and differences in vaccine communication strategies employed by the two publications, as well as the dynamics between discursive practices, social-political contexts, and underlying ideologies. While The New York Times focuses primarily on addressing domestic vaccine hesitancy, People's Daily aims to secure wide international recognition for Chinese vaccines and to highlight China's contribution to global health efforts. This study suggests that both newspapers should adopt a more collaborative mindset to effectively combat COVID-19 and enhance health communication strategies.